High Definition 2-dimensional Numerical Model of Particle Settling on Newtonian and Shear-Thinning Fluids (Annual Transactions of the Nordic Rheology Society, 2024)
Well-defined particle sedimentation can provide relevant information in characterizing non-colloidal suspension. Nonetheless, the interaction between phases can become extremely convoluted as agglomerates are formed and broken, dynamically creating regions of high and low shear-rate. Numerical simulations are an alternative to obtain detailed descriptions of said interactions. In this work, the lattice-Boltzmann method is used together with the discrete element method to solve for two-dimensional sedimentation problems for both Newtonian and shear-thinning fluids.